Match Characteristics of Regional Medical Campus and Main Campus Students by Residency Program Type and Location - Emily Schaff; Andrea Espinosa; Aaron Meers; Jackson Taylor; David Haustein (Journal of Regional Medical Campuses)
Background and Objectives: In response to the AAMC’s call to increase the number of medical school graduates in 2006, there has been a steady growth in the number of medical schools offering some or all of the medical education curriculum at regional medical campuses (RMC) across the country with 133 medical schools reporting a RMC in 2023.1 Additionally, RMC expansion plans were reported by 25 medical schools in a 2020-2021 survey.2 Because of this increase in the number of medical students attending RMCs, studies must be conducted to determine if attending a RMC influences matching into residency programs by location (in-region or out-of-region) and program type (community-based, university, etc.). This study aims to investigate this possible correlation between the University of Missouri School of Medicine (MUSOM) main campus in Columbia, Missouri, and its RMC in Springfield, Missouri.